(untitled) (Transport systems and technologies, 2020)
The role of maritime transport in world trade cannot be overemphasized. In developed industrialized countries, the transportation system represented by all main modes of transport, but the share of their use differs significantly for some regions and particular countries. Despite the leading position of land transport modes, maritime transport remains the most economically advantageous for solving the freight transportation tasks in intercontinental traffic. When it comes to the transportation of special, unique and expensive cargoes such as oversized cargoes, maritime transport is given clear preference in the comparative characteristics of delivery cost between adjacent modes of transport, taking into account the long distances. High carrying capacity also significantly differentiates between maritime transport and land or air transport. Other things being equal, the cost of maritime as well as multimodal transport is lower than the cost of land transport. The study of the issues of classification of goods by various characteristics and the relationship of the transport condition of cargo with the technology and organization of the transport process by sea transport is an actual task. Characteristic features such as the transport characteristics of the cargo allow estimating those properties, which somehow influence the organization and choice of technology of sea transportation. In order to carry out transportation of oversized cargoes, the choice of a vessel must be stipulated taking into account the specialization of the vessel for such transportation or development of a methodology to justify the selection of a non-specialized vessel in cases where it is practicable. Such transportations can be performed with the use of bulk carriers with excess free tonnage observed in regions and countries of consumers of bulk cargoes and exporting rolled metal products and equipment.